Histological Study of the External, Middle and Inner Ear of Horses. (6th October 2014) - Blanke, A.; Aupperle, H.; Seeger, J.; Kubick, C.; Schusser, G. F.
Summary Clinical, anatomical and histological aspects of the equine acoustic organ have been poorly investigated and illustrated in literature so far. It is understood that an intact acoustic organ and hearing function are of vital importance for the well‐being of flight animals like horses. The knowledge of the acoustic organ is usually transferred analogously from other mammals to horses. The purpose of this study was to provide a detailed and complete histological description of the healthy equine auditory organ, and to determine its congruity to other mammalians. Anatomical dissections and histological preparations were carried out on ten cadaver heads. Specimens of various parts of the equine acoustic organ were taken and evaluated histologically. The histological composition of external, middle and inner ear structures are predominantly congruent to those of other mammals, especially to human beings. Unique inwardly directed rete pegs within the osseous ear canal and the prominent tensor tympani muscle are described for the first time. Results obtained in this study can be employed as references for further research on the equine acoustic organ and improve the understanding of the clinical development of hearing loss, otitis externa/media/interna or tympanosclerosis.